2018
DOI: 10.3390/en11010175
|View full text |Cite
|
Sign up to set email alerts
|

Coal Matrix Deformation and Pore Structure Change in High-Pressure Nitrogen Replacement of Methane

Abstract: Abstract:Coal matrix deformation is one of the main controlling factors for coal reservoir permeability changes in nitrogen foam fracturing. The characteristics and mechanism of coal matrix deformation during the process of adsorption/desorption were studied by isothermal adsorption/desorption experiments with methane and nitrogen. Based on the free-energy theories, the Langmuir equation, and elastic mechanics, mathematical models of coal matrix deformation were developed and the deformation characteristics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition, the amorphous surface of coal enriches functional groups, possessing strong adsorption capacity for polar molecule adsorbates [5][6][7], such as water vapor. In coal preparation and utilization processes, including coalbed methane (CBM) recovery and CO 2 geosequestration, both surface properties and pore structure are important aspects to be investigated [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the amorphous surface of coal enriches functional groups, possessing strong adsorption capacity for polar molecule adsorbates [5][6][7], such as water vapor. In coal preparation and utilization processes, including coalbed methane (CBM) recovery and CO 2 geosequestration, both surface properties and pore structure are important aspects to be investigated [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that some of the gas remained in the coal after gas desorption. Previous research found that the coal matrix will swell or shrink after gas adsorption–desorption, and the pore structure and distribution characteristics of coal will change . In this part, the pore structure of low-pressure gas adsorption was tested.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research found that the coal matrix will swell or shrink after gas adsorption− desorption, and the pore structure and distribution characteristics of coal will change. 36 In this part, the pore structure of low-pressure gas adsorption was tested. Meanwhile, the deformation characteristics of different types of nanopores were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Methane productivity of some CBM wells is quite low and even did not produce gas in part wells, which like Z-7H, Z-159, and Z-163 wells in the experiment. Gas foam fracturing has been used in these wells to expand crack and improve coal permeability (Ji et al 2018). However, the effect was not satisfying.…”
Section: Introductionmentioning
confidence: 99%